An Assessment of Total Factor Productivity (TFP) of SME Business in Bangladesh using DEA based Malmquist Productivity Index (MPI) - Jianguo, WEI; Qamruzzaman, Md. (ABC Journal of Advanced Research, 2017)
For sustainable growth, SMEs play a dynamic role through creation of employment, increase of aggregate production, maximization of economic resources in the economy.  Considering SMEs impact on diversified area of economy, the subject matter of SMEs productivity draw intense attention for intense research over last decade. In Bangladesh, as developing country, SMEs contribution becoming significant for employment generation, reduce income inequalities and lead to export through maximization of production. The objective of this study to assess SMEs performance for the period from 2005 to 2014. Study measures productivity using Malmquist Productivity Index (MPI) having one outputs and three inputs.  We run regression analysis to identify residual by comparing expected output and an actual output having available inputs. Study result revealed that productivity index (MALM = 1) remains constant, but it is found that technical efficiency enhancement from 2010 to 2014, however overall efficiency declined by 2.6% as well. The residual analysis revealed no significant deviation between expecting output and actual output by using available inputs. This research outcome will give a glimpse about overall SME performance, which will induce researchers to go further in-depth analysis for bringing more insight for SME development.